Homophobia in Poland and Hungary: Assessing its Political Motives and Influences - Hanley, Thomas (Colloquium: The Political Science Journal of Boston College, 2017)
Since World War II, Europe has historically been recognized as a pillar of social liberality. Yet recently, Hungary and Poland have elected governments and enacted policies that are fiercely homophobic. This paper will look to understand the political motives and influences behind the recent turn to homophobia in both countries. First, the paper will explain Hungary and Poland’s unique position between the socially liberal European Union and a socially conservative Russia. Both parties compete for influence in domestic Hungarian and Polish politics, with the European Union hoping to solidify its ideological border against Russia and the Kremlin hoping to create centers of influence within the EU. The second portion of the paper will argue that both Polish and Hungarian homophobia is a rejection of the European Union – used as a political tool to reestablish national control from Brussels. And lastly, the paper will explore the role of Vladimir Putin’s Russia in that rejection – arguing that Putin holds significant influence in Hungarian homophobia, as Viktor Orbán’s government is closely tied with the Kremlin. Yet, the paper concludes that the situation is quite different in Poland – where relations with Russia are not nearly as cordial, arguing that the Polish Catholic Church is much more responsible for the socially conservative policy.